The Analysis of Speech Error in King George VI in the Movie “King’s Speech” By David Seidler - Riskiawati, Nur Sapta; Razak , Muhammad Fauzi (Formosa Journal of Applied Sciences, 2024)
This paper explores the speech errors made by King George VI in David Seidler's "The King's Speech." The study seeks to identify these errors and describe the treatments used to remedy them. Adopting a qualitative method, with a psycholinguistic approach, note-taking is employed as the primary tool for data collection through watching of movie clips, reading script materials, categorizing data based on applicable theories. Timely resolution needs addressing relevant issues before they become regular habits. This thesis serves an integral purpose within English Literature research-education thus proving highly beneficial among students alike-unlocking epistemic learning potentiality assessments concerning this category English literature genre.